PENGARUH KEPUASAN KONSUMEN TERHADAP KESETIAAN MEREK (STUDI KASUS CITARASA BAKERY BONTANG) - Tria Juliastuti; Gusti Noorlitaria A; Saida Zainurossalamia Z.A (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
The purpose of this study was to determine the effect of customer satisfaction on brand loyalty. The analysis tool used in this study is multiple regression analysis consisting of multiple linear regression tests, correlation test (R), test coefficient of determination (R2). The results showed a positive and significant relationship between customer satisfaction with brand loyalty. With the results of the research showing positive and significant influences t, it is sufficient to support the theory.